Determination of radiocarbon in environmental objects - Аlmira Raimkanova; Ainur Mamyrbayeva; Аlmira Aidarkhanova; Аssan Aidarkhanov; Aidana Sarsenova; Zhanna Tleukanova (PLoS ONE, 2025)
This article presents the results of radiocarbon distribution in natural components of ‘Degelen’ test location. It was used to conduct underground nuclear tests at the Semipalatinsk Test Site. Near-entry areas with water inflows were selected for research. Soil, plant and water samples were taken, in which the radiocarbon content was determined. The 14С activity concentration was determined using a highly sensitive alpha-beta radiometer SL-300 (ISO 13162, 2021). Sample preparation was carried out using a modern automated system Pyrolyser-6 Trio (Raddec International Ltd, UK). In the course of research undertaken, radiocarbon was revealed to be nonuniformly distributed in environmental objects. The effectiveness of Pyrolyser-6 Trio calcination and ashing system for 14C determination in environmental matrices has been demonstrated.